2014
DOI: 10.1093/heapol/czu047
|View full text |Cite
|
Sign up to set email alerts
|

The use of counting beads to improve the classification of fast breathing in low-resource settings: a multi-country review

Abstract: To decrease child mortality due to common but life-threatening illnesses, community health workers (CHWs) are trained to assess, classify and treat sick children. For pneumonia, CHWs are trained to count the respiratory rate of a child with cough and/or difficulty breathing, and determine whether the child has fast breathing or not based on how the child’s breath count relates to age-specific respiratory rate cut-off points. International organizations training CHWs to classify fast breathing realized that man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 3 publications
(3 reference statements)
1
23
0
Order By: Relevance
“…Beyond 65 min –1 , the device need only display a ‘high’ readout, indicating tachypnoea and the need for antibiotic treatment. Previous studies have shown that CHWs sometimes have a difficult time interpreting numerical results and applying the RR appropriately to the ICMI treatment algorithm to determine appropriate candidates for antibiotic treatment 24. As such it has been recommended by the Unicef TPP that a device that provides automated results with a high level of treatment decision support is preferable 16 19.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond 65 min –1 , the device need only display a ‘high’ readout, indicating tachypnoea and the need for antibiotic treatment. Previous studies have shown that CHWs sometimes have a difficult time interpreting numerical results and applying the RR appropriately to the ICMI treatment algorithm to determine appropriate candidates for antibiotic treatment 24. As such it has been recommended by the Unicef TPP that a device that provides automated results with a high level of treatment decision support is preferable 16 19.…”
Section: Discussionmentioning
confidence: 99%
“…When measured by primarily illiterate community health workers in Uganda and South Sudan, it was found the rate of correctly classifying fast breathing in children increased from 27% to 68% when using the counting beads. 321 While counting techniques have shown great improvements in the ability to accurately detect fast breathing, automated devices that decrease the time burden on health care workers could further improve pneumonia detection. Some wearable, continuous infant monitoring devices have been developed (for example, the Rest Devices’ Mimo and Snuza® Hero MD ), but these devices remain prohibitively expensive for use in low-resource settings, as the per device costs range from$150 - $300.…”
Section: Diagnostics For Neonatal Healthmentioning
confidence: 99%
“…(b) Bead strand used by UNICEF that is non-specific for ages 0–5 years and each color is made up of 10 beads for ease of counting. Reprinted from Reference 321 under the terms of Creative Commons Attribution License.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations